Spatial Analysis of Socio- Economic Inequalities Based on Multidimensional Welfare Indicators, Case study: Zahedan Urban Neighborhoods - zahra sargazi; alireza mohamadi; golamali khammar (جغرافیا و توسعه, 2021)
Nowadays, cities are places for the economic development of societies, and as cities have human existence, they are one of the challenges of the fight against poverty to provide the proper infrastructure for economic growth and promotion. Focusing on enhancing multidimensional welfare indicators can minimize issues such as economic and social inequalities in the city. The aim of this study is spatial analysis of socio-economic inequalities of Zahedan based on multidimensional welfare indicators. In this study, multidimensional welfare indicators were measured in 55 dimensions in two dimensions of material welfare. In order to spatial analysis of multidimensional welfare indicators after normalization, welfare differences in urban neighborhoods were calculated and the results were prepared in the form of difference coefficient maps. Finally, the relation between the level of welfare and the coefficient of difference was evaluated using Pearson's statistical test. The results showed that the neighborhoods with the more welfare are located in district one and five in southwest of Zahedan and the north and south suburbs of Zahedan are in more undesirable condition than other urban areas. The results of correlation test between multidimensional welfare level and welfare difference coefficient also show that at alpha level of 0.1 there is only significant relationship between non-material welfare and housing components, access to services, infrastructures and facilities and knowledge with their difference coefficient. However, at Alpha level of 2 there is a significant relationship between material and immaterial welfare and housing components, access to services, health and knowledge with their difference coefficient.